2018
DOI: 10.3390/nano8050305
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Physicochemical Properties of Newly Formed ZnO-PMMA Nanocomposites for Denture Bases

Abstract: Aim: The aim of this study was to investigate the selected properties of zinc oxide- polymethyl methacrylate (ZnO-PMMA) nanocomposites that can influence the microorganism deposition on their surface. Materials and Methods: Non-commercial ZnO-NPs were prepared, characterized and used for the preparation of PMMA nanocomposite. Roughness, absorbability, contact angle and hardness of this new nanomaterial were evaluated. PMMA without ZnO-NPs served as control. Outcomes: Compared to unenriched PMMA, incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 34 publications
(43 reference statements)
1
47
0
5
Order By: Relevance
“…Selective doping that enables controlling the semiconductor properties of ZnO, such as conductivity or forbidden band, has made it an interesting material for potential application in electronics, spintronics and optoelectronics. The biocompatibility, antibacterial and antifungal action of ZnO are the reasons it enjoys large interest in pharmacy and biomedicine [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. It is a common ingredient of everyday products, e.g., rubber, pigments, cements, plastics, paints, pharmaceutical products and cosmetics [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Selective doping that enables controlling the semiconductor properties of ZnO, such as conductivity or forbidden band, has made it an interesting material for potential application in electronics, spintronics and optoelectronics. The biocompatibility, antibacterial and antifungal action of ZnO are the reasons it enjoys large interest in pharmacy and biomedicine [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. It is a common ingredient of everyday products, e.g., rubber, pigments, cements, plastics, paints, pharmaceutical products and cosmetics [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wei ZOU 1 , Guang HONG 2,3 , Yukiko YAMAZAKI 1 , Kazuma TAKASE 4 , Toru OGAWA 1 , Jumpei WASHIO 5 , Nobuhiro TAKAHASHI 4 and Keiichi SASAKI 1 Table 1 The immersion solutions used in this study it indicates the ease by which saliva spreads over the surfaces. It is reported that a denture base material with higher wettability should be the primary choice for clinical application 10) .…”
Section: Use Of Cellulose Nanofibers As a Denture Immersing Solutionmentioning
confidence: 99%
“…Polymethyl methacrylate (PMMA), a polymer-based material introduced in the 1930s, has been most commonly used for the fabrication of dentures. From a clinical point of view, PMMA has acceptable mechanical and biological properties, satisfying aesthetic performance, and a clearly-defined processing method 2) .…”
Section: Introductionmentioning
confidence: 99%
“…PMMA also exhibits an amorphous polymer processing dimensional stability that allows it to be used as a host in composite material fabrication [1]. Various PMMA composite materials with desired properties were reported such as functional transparent composites [2][3][4] and infrared (IR) shielding composites [5].…”
Section: Introductionmentioning
confidence: 99%